Leadership in science and technology : a reference handbook - Bainbridge, William Sims. (Los Angeles : SAGE, 2012)
'This 2-volume set within the SAGE Reference Series on Leadership tackles issues relevant to leadership in the realm of science and technology. To encompass the key topics in this arena, this handbook features 100 topics arranged under eight headings. Volume 1 concentrates on general principles of science and technology leadership and includes sections on social-scientific perspectives on S&T leadership; key scientific concepts about leading and innovating in S&T; characteristics of S&T leaders and their environments; and strategies, tactics, and tools of S&T leadership. Volume 2 provides case studies of leadership in S&T, with sections considering leadership in informal communities of scientists and engineers; leadership in government projects and research initiatives; leadership in industry research, development, and innovation; and finally, leadership in education and university-based research. By focusing on key topics within 100 brief chapters, this unprecedented reference resource offers students more detailed information and depth of discussion than typically found in an encyclopedia entry but not as much jargon, detail or density as in a journal article or a research handbook chapter. Entries are written in language and style that is broadly accessible, and each is followed by cross-references and a brief bibliography and further readings. A detailed index and an online version of the work enhances accessibility for today's student audience'--
Machine generated contents note: 005. Advice to Government - William Blanpied.
Includes bibliographical references and index.
Keywords: Scientists; Technologists; Science; Technology; Leadership; Leadership -- Case studies